Verska in jezikovna raznolikost in (ne)strpnost v 18. stoletju – Ziljski (podtalni) protestanti na prehodu v tolerančno obdobje - Domej, Theodor (Slavia Centralis, 2020)
Religious and Linguistic Diversity and (In)Tolerance in the 18th Century – the (Underground) Protestants from Gailtal at the Transition from “Underground” Religious Life to the Age of ToleranceA small group of Protestants, named after the Carinthian village Agoritschach (Zagoriče) at the foot of the Karawanks on the today’s border between Austria, Italy and Slovenia, was the only Slovene Protestant community in the territory of the Habsburg hereditary lands in the first period after the publication of the Edict of Tolerance (1781). For two centuries, the group preserved its forbidden faith and cultivated it with the help of Slovene prints and manuscripts. According to the contemporary regulations, too small to be organized as an independent religious community, it joined the German speaking community of Bleiberg. The article analyses linguistic and ethnic issues in the pre-national period. It shows how the leading representatives of the Bleiberg Protestant community viewed the Slovene group and Slovene language. It also deals with the efforts to publish some basic Protestant books in Slovene.
Keywords: Carinthia (Austria); Protestants; Slovene language; book project; identity